Loss of the fructose transporter SLC2A5 inhibits cancer cell migration - Groenendyk, Jody; Stoletov, Konstantin; Paskevicius, Tautvydas; Li, Wenjuan; Dai, Ning; Pujol, Myriam; Busaan, Erin; Ng, Hoi Hei; Boukouris, Aristeidis E.; Saleme, Bruno; Haromy, Alois; Cui, Kaisa; et al. (Frontiers in Cell and Developmental Biology, 2022)
Metastasis is the primary cause of cancer patient death and the elevation of SLC2A5 gene expression is often observed in metastatic cancer cells. Here we evaluated the importance of SLC2A5 in cancer cell motility by silencing its gene. We discovered that CRISPR/Cas9-mediated inactivation of the SLC2A5 gene inhibited cancer cell proliferation and migration in vitro as well as metastases in vivo in several animal models. Moreover, SLC2A5-attenuated cancer cells exhibited dramatic alterations in mitochondrial architecture and localization, uncovering the importance of SLC2A5 in directing mitochondrial function for cancer cell motility and migration. The direct association of increased abundance of SLC2A5 in cancer cells with metastatic risk in several types of cancers identifies SLC2A5 as an important therapeutic target to reduce or prevent cancer metastasis.